ANALISIS RESPON MAHASISWAPGSD DALAM MENYELESAIKAN SOAL IPABERDASARKAN STRUCTURE OF OBSERVED LEARNING OUTCOME TAXONOMY DITINJAU DARI MOTIVASI BELAJAR - Siti Fatimah (Universitas Negeri Padang, 2017)
SOLO Taxonomy is one of the frameworks used in analyzing the quality of responses in problem solving. This research aim to analyze the student’s responses level in doing problem solving item based on SOLO Taxonomy overviewed from motivation to learn. The research method used in this study was a qualitative research with the data sources of this study were 75 students period 2016/2017. The results of the study showed that student’s responses in doing problem solving wave concept at prestructural level is 62,17%, Unistructural Level is 27,63%, Multistructural level is 58,22%, Relasional level is 48,50%, and Extended Abstract level is 37,82%; Motivation to learn’s student high category are better at responding to answer item based SOLO Taxonomy than motivation to learn’s students low category.Keywords: Student’s reponses; SOLO Taxonomy; Motivation to Learn